Global trends and hotspots in research on osteoporosis rehabilitation: A bibliometric study and visualization analysis - Wang, Liqiong; Jiang, Jiaojiao; Li, Yi; Huang, Jinming; Wang, Renjie; Liang, Yuxiang; He, Chengqi; Liu, Shaxin (Frontiers in Public Health, 2022)
Background The field of rehabilitation medicine plays an essential role in the comprehensive management of osteoporosis and its consequences. The benefits of therapeutic exercise are increasingly being recognized in this area, which receives an increasing number of publications. this study was designed to comprehensively identify collaborative networks, parse and track research trends, spotlight present hotspots, and accurately predict frontiers and focus on the health topics related to osteoporosis rehabilitation. Methods This research adopted computer retrieval of osteoporosis rehabilitation-related research published in the Web of Science Core Collection (WoSCC) from inception to June 14, 2022. The bibliometric visualization and comparative analysis involving countries, institutions, journals, authors, references, and keywords were performed using the CiteSpace and VOSviewer software. Results A total of 3,268 articles were included, and the number of articles published each year has demonstrated a steady increase. The United States and the University of Melbourne were the highest productive country and institution, with 1,325 and 87 articles, respectively. The journal of osteoporosis international has published the greatest number of articles, with 221 publications, and the journal of bone and mineral research ranked first in the co-citation counts (cited by 11,792 times). The most productive and highly-cited authors were Heinonen A and Cummings S, with 35 publications and 680 citations. Conclusions At present, “physical activity,” “weight bearing exercise,” “muscle strength,” “whole body vibration,” “postmenopausal women,” “older women,” children, men are the noteworthy research hot topics. Future research that focus on the major modes and parameters of physical activity/exercise for osteoporosis (including whole body vibration, weight bearing exercises, resistance training), targeted multicomponent training regimens, rehabilitation therapy for postmenopausal women, older women, children and men, osteoporosis related-sarcopenia and fractures, and mesenchymal stem cells are becoming frontiers and focus on the health topics related to osteoporosis rehabilitation in the upcoming years, which are worthy of further exploration.